Structure and Morphological Properties of In2O3 Nanostructure Prepared by Pulse Laser Ablation Method - ALgawi, Sariya D. AL.; Khalef, Wafaa K.; Mohammed, Sura R. (Iraqi Journal of Science, 2018)
A colloidal indium oxide (In2O3) nanoparticles (NPs) were synthesized pulsed laser ablation (PLA) of indium plate placed on the bottom of the quartz vessel containing (3ml) of pure ethanol. The influence laser energy on the properties of the formed nano-particles were characterized by using atomic force microscopy (AFM), X-ray diffraction (XRD), Ultraviolet Visible (UV-Vis) technique, and electrical properties measurements. The XRD revealed the crystallization structure of In2O3 nanoparticles and all the films having preferential orientation along (222) plane and intensity increases with increasing laser energy, The UV–Visible spectrum of the colloidal nanoparticles maximum absorbance show around the UV region, which indicates the formation of In2O3 nanoparticles with energy gap about (3.6, 3.8 and 3.9) eV for different laser energy's (150, 300 and 500) mj respectively. The film conductivity decreased with increasing laser energy, while increasing in the the activation energy of In2O3 nanopartical.